2009
DOI: 10.1029/2009gl040494
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic capture of 1 Hz volcanic SO2 fluxes and integration with volcano geophysical data

Abstract: Here we present a novel spectroscopic approach to capturing, with unprecedented time resolution and accuracy, volcanic SO2 fluxes. This is based on two USB2000 spectrometers, coupled to cylindrical lens telescopes, each collecting light which has transited horizontal sections of the rising plume. We report on field data from Stromboli volcano, in which the entire emission rate from the volcano was measured, as well as flux signatures associated with individual crater explosions. The latter were integrated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 22 publications
3
59
0
Order By: Relevance
“…Moreover, the low time resolution of both techniques hampers detection of flux changes related to transient (≤tens of seconds) degassing-driven volcanic phenomena, such as strombolian and vulcanian explosions (McGonigle et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low time resolution of both techniques hampers detection of flux changes related to transient (≤tens of seconds) degassing-driven volcanic phenomena, such as strombolian and vulcanian explosions (McGonigle et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The first report of high time resolution (≈1 Hz) degassing data being corroborated with geophysical data concerned explosions on the Stromboli volcano [41]. This study was performed using spectroscopy, rather than UV imaging, but, in common with a more recent UV camera study on this target [49], it revealed linear correlations between the magnitudes of the recorded degassing, thermal, and very long period (VLP) seismic signatures for the events.…”
Section: Combination Of Uv Camera Degassing Data With Geophysical Datmentioning
confidence: 79%
“…Whilst this has been achieved spectroscopically with high temporal resolution differential optical absorption spectroscopy observations [41], and even with a correlation spectrometer [47], it is far easier to resolve these emissions with the cameras' imaging capacity. The eruptions where SO 2 masses have been constrained with UV imagery have been ash-poor, strombolian, or weakly vulcanian events.…”
Section: Improving the Spatio-temporal Resolution Of Volcanic Degassingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the possibility of non-aliased corroboration between volcanic degassing and geophysical (≈1 Hz) data streams, as recently achieved with a related approach by McGonigle et al (2009), offers promise to significantly deepen our volcanological understanding. Earlier attempts at such multi-parametric analyses, albeit on the basis of the then available far coarser time resolution SO 2 fluxes, have confirmed the great potential contained therein (e.g., Fischer et al, 1994;Watson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%